THE PRINCIPAL TYPES OF ENGLISH PRONUNCIATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The main forms of English pronunciation, an area of research essential to phonetics and sociolinguistics, are systematically summarized in this article.  While recognizing the importance of other national and regional standards, it looks at the historical development and distinguishing phonological characteristics of the two most significant reference accents, Received Pronunciation (RP) and General American (GenAm).  The conversation emphasizes how crucial it is to comprehend pronunciation diversity in the context of academic instruction and international English communication.